Empowering Orphanage Children Through Entrepreneurship Training Based On Local Beverage Products: A Case Study Of Pineapple And Ginger Syrup Production - Wahyudi Ilham (JURNAL KEKER WISATA, 2025)
This community service program aims to empower orphanage children through practical entrepreneurship training focused on utilizing local natural resources. Conducted at Al Amani Orphanage in Batam, the program introduced participants to the process of producing pineapple and ginger syrup, two locally available ingredients with economic potential. The training covered stages from material preparation, production, packaging, to simple marketing strategies. The objective was to develop entrepreneurial spirit, creativity, and confidence among the children, while also encouraging awareness of the value of local resources in economic activities. Results showed a significant increase in participants’ understanding of product development and interest in entrepreneurship. The program not only provided essential skills but also served as a foundation for future economic self-reliance initiatives in orphanage communities.